Sufism Symbol ( Mark ) Between Concrete Basis And Spiritual Event - سليطين علي; ميساء علي (Latakia University Journal - Arts and Humanities Sciences Series, 2024)
A Human with his nature is a remarkable creator. He liked to hide his secrets and expressing his thoughts or believes through symbols he has found especially when these symbols function as a measurement for civilization and evolution on different levels. Thus they are divided in many direction where it’s hard to gather its limits accumulated. Symbols are not the same in one level or one way , they are different from age to another as well . Sometimes different are existed in the same period of time . They could be difficult , clear and easy also. So symbols could express sometimes what you can’t say in clear and direct words especially in Sufism world where should be out of sorts and nature to reach that meaning of redemption through denial of existence and accept the real fact , which cause the different levels of symbols that hasn’t noticed in human history . Those symbols are harmonized with the spiritual _ realized Sufist . So, a word adopt a different meaning that replies to an abstract meaning which is different from the concrete one .